`He found me very well; for me, I was still feeling sick': The strange worlds of physicians and patients in the 18th and 21st centuries. Issue 1 (1st June 2002) - Louis-Courvoisier, M; Mauron, A
Abstract : It is commonplace today to deplore the dissatisfaction of patients with the physician-patient relationship. Furthermore, historical investigation shows that this problem is not really new. We investigated an important source of patients' views in the 18th century, namely the letters of patients received by the famous Swiss physician, Samuel Tissot, and noted remarkably similar feelings of frustration. Yet the medical paradigms of today and of Tissot's times are considerably different. We propose that the persisting problems in the physician-patient relationship are due to a basic dissonance between the patient's ordinary modes of perception and the systematic way of perceiving reality characteristic of the physician. In addition, they reflect the unavoidable chasm between the ultimately private and singular nature of the illness experience, and the general and anonymous stance of medical theory. This chasm is therefore a permanent feature of the patient-physician relationship, predating the advent of scientific medicine, even if the latter reinforced it. In line with the current medical humanities movement, we believe that the engagement of physicians and medical students with literature and the arts helps them explore, and to some extent overcome, the existential divide between the patient's experiential self knowledge and the systematic, impersonal knowledge that plays a central role in medicine. We suggest a few examples of contemporary fiction that may be relevant and useful in this respect.